Autoimmune hypophysitis: A case report (Indian Journal of Case Reports, 2019)
Autoimmune hypophysitis is an autoimmune inflammation of the pituitary gland. It may result in hypopituitarism depending upon the part of pituitary affected. Here, we report the case of autoimmune hypophysitis in a 30-year-old male who was admitted with complaints of generalised swelling for one month and fever and cough for one week. The patient’s Thyroid-stimulating hormone (TSH) was more than 139, anti-thyroid peroxidase antibody (anti-TPO) was more than 1000 and serum sodium was 107 and a tiny streak of tissue along the periphery with an empty sella as seen on MRI. The patient was given tablet Levothyroxine 100 microgram, Telmisartan 40 mg and Hydrocortisone 10mg twice daily. With medications, the patient improved and was discharged.